Activated TNF-α/RIPK3 signaling is involved in prolonged high fat diet-stimulated hepatic inflammation and lipid accumulation: inhibition by dietary fisetin intervention. Issue 3 (22nd February 2019) - Xu, Minxuan; Ge, Chenxu; Qin, Yuting; Gu, Tingting; Lv, Jinxiao; Wang, Sujun; Ma, Yongjie; Lou, Deshuai; Li, Qiang; Hu, Linfeng; Nie, Xuyuan; Wang, Mingxing; et al.
Abstract : Increasing evidence indicates that high-fat diet (HFD) is a predisposing factor for metabolic syndrome-associated systemic inflammation and nonalcoholic fatty liver disease (NAFLD). Abstract : Increasing evidence indicates that high-fat diet (HFD) is a predisposing factor for metabolic syndrome-associated systemic inflammation and nonalcoholic fatty liver disease (NAFLD). Tumor necrosis factor-α/receptor-interacting protein kinase 3 (TNF-α/RIPK3) axis has recently become regarded as an important regulator and contributor in many inflammation-related diseases. Fisetin (Fn) is a bioactive flavonoid polyphenol with anti-inflammatory and anti-tumor activity. Lately it has gained increasing attention due to its potential advantages in prevention of tumors, metabolic disorders, neuroinflammation and chronic liver injury. However, its role in NAFLD is still not fully understood. Thus, we studied whether prolonged HFD causes TNF-α/RIPK3 activation-associated hepatic steatosis, further evaluating the protective effects of Fn in HFD-fed mice. As expected, HFD promotes metabolic syndrome and pro-inflammatory cytokine generation in serum, enhances liver inflammatory infiltration-related lipid accumulation by increase of TNF-α/RIPK3 activation, ultimately resulting in development of nonalcoholic steatohepatitis. In contrast to this, dietary Fn intervention could suppress metabolic disorder and HFD-triggered hepatic function loss, downregulate TNF-α/RIPK3 signaling-associated hepatic inflammation, balance lipid metabolism-related gene expression, and finally inhibit lipid accumulation and steatohepatitis. Hence, Fn restrains HFD-induced hepatic inflammation and lipid deposition by downregulating metabolic disorder and excessive liver inflammation-associated TNF-α/RIPK3 axis activation.